THEMATIC STRUCTURE OF SPORT TEXTS IN WASPADA NEWSPAPER - Widya Astuti (Universitas Islam Sumatera Utara (UISU), 2018)
This study was conducted to describe the thematic structure in the news of Waspada Newspaper. The objectives of the study are 1) to describe the types of themes which are used in the sport texts of Waspada Newspaper and 2) to find the reasons why the structure of themes used in the ways they are. This study was conducted in descriptive qualitative design. The source of data was obtained from the clauses in sport texts of Waspada that consists of six sport texts. In analyzing the thematic structure, there are three kinds of theme: textual, interpersonal and ideational or topical. It was taken by applying documentary technique. The findings showed that unmarked multiple theme is the most dominant, unmarked simple theme is the second one Comparing with other themes, the marked multiple theme gets the third while the marked simple theme is the least dominant theme in sport texts of Waspada newspaper.